Using Pair Composition Method to Improve the Students' Descriptive Writing skill: Using Pair Composition Method to Improve the Students' Descriptive Writing skill - Miranda Eka Tama; Yuspar Uzer; Yus Vernandes Uzer (Holistics (Hospitality and Linguistics) : Jurnal Ilmiah Bahasa Inggris, 2022)
This study is about investigating the application of the pair composition method in increasing the interest in learning of senior high school 12 of Palembang students in writing. The research question is to find out if there was any significant difference between the students who were taught writing using pair composition method to improve their descriptive writing skill at the tenth grade students of state Senior High School 12 of Palembang and those who were not. This study can conclude that using the Pair Composition Method can increase students' grades and interest in learning. Based on the test results, students who were taught by used the Pair composition method in writing descriptive text got a more significant score. Keywords: Pair composition method, descriptive writing